Low Dose Interleukin-2 Ameliorates Sjögren’s Syndrome in a Murine Model - Wang, Yifan; Feng, Ruiling; Cheng, Gong; Huang, Bo; Tian, Jiayi; Gan, Yuzhou; Jin, Yuebo; Miao, Miao; Zhang, Xia; Sun, Xiaolin; He, Jing; Li, Zhanguo (Frontiers in Medicine, 2022)
Sjögren’s syndrome (SS) is a systemic autoimmune disease with no efficient treatment, and it is associated with dysregulated immune cells and impaired interleukin (IL)-2 signaling. IL-2 is critical for the development and maintenance of Treg cells. The use of low dose of IL-2 (LDIL-2) in the treatment of autoimmune diseases is promising, but the efficacy and mechanism in SS therapy are still to be confirmed. This study aims to investigate the therapeutic effect of LDIL-2 on SS in NOD (non-obese diabetic) mice. NOD mice (female, 8 weeks old) were randomly assigned into three groups (n = 8). Low dose of IL-2 (LDIL-2), high dose of IL-2 (HDIL-2), and isometric sterile water (control) were administered subcutaneously daily from week 8 to week 16. LDIL-2 administration significantly recovered the reduction in saliva flow and suppressed lymphocyte inflammation of the submandibular glands (SMGs) when compared with those treated with sterile water as controls (p < 0.05). SS related biomarkers including ANA, Anti-SSA/Ro, and Anti-SSB/La also declined (p < 0.05). In the low dose of IL-2 treated group, the proportion of CD4+CD25+Foxp3+Tregs in both spleen and cervical-lymph-node were higher than control mice (p < 0.05). Furthermore, CD4+Bcl-6+PD-1+CXCR5+Tfh cells, CD4+IFN-γ+Th1 cells, and CD4+IL-17A+Th17 cells were significantly reduced in LDIL-2 group (p < 0.05). Analysis of the SMGs biopsies showed significantly decreased inflammation scores after LDIL-2 administration and an increase of Tregs with immunohistochemical staining. Our findings provide in vivo evidence that LDIL-2 was an effective therapeutic intervention for SS observed in NOD mice and may restore immune balance through the promotion of Treg and suppression of germinal center (GC) B cells and effector T cells.